Activity-Based Budgeting: Innovative Budgeting or an Efficiency Illusion? : A Systematic Literature Study - Sivano, Tamara Theresia; Sinta, Clara; Rizkiyah, Miftahul; Vanesca, Naqiyyah Ghina Kurnia; Sulbahari, Rifani Akbar (Pustaka Peradaban, 2026)
This study evaluates the effectiveness of Activity-Based Budgeting (ABB) and Activity-Based Management (ABM) implementation to determine whether these systems constitute a strategic innovation or merely an illusion of efficiency. Employing a Systematic Literature Review (SLR) methodology in accordance with the PRISMA 2020 protocol, this research synthesizes 19 internationally reputable articles published between 2011 and 2025. The findings reveal a significant dialectic in global budgeting practices; while the majority of the literature positions ABB/ABM as a genuine innovation that enhances cost accuracy and resource transparency, the study also uncovers an